Airborne sound insulation of vacuum insulating glazing: General observations from measurements. Issue 3 (September 2016) - Cabrera, Densil; Ashmore, Nathan; Kocer, Cenc
Vacuum insulating glazing can be very effective as a thermal insulator, which makes it potentially useful in reducing energy loss through building facades. This article examines its effectiveness for airborne sound insulation. Measurements of intensity sound reduction index were made of samples of single glazing and commercially manufactured vacuum insulating glazing, which showed that vacuum insulating glazing (made from pairs of panes with the same thickness) followed mass law principles in the low-frequency range, with a deep coincidence dip in mid-to high-frequency region. The coincidence dip occurred at the frequency for an individual constituent pane. The coincidence dip was reduced or removed by clamping another pane of glass to the vacuum insulating glazing sample. The resulting airborne sound insulation rating of the augmented vacuum insulating glazing samples is substantially improved and comparable to ratings achieved by other thin window airborne sound insulation techniques.